2016
DOI: 10.7717/peerj.2428
|View full text |Cite
|
Sign up to set email alerts
|

Identifying suitable reference genes for gene expression analysis in developing skeletal muscle in pigs

Abstract: The selection of suitable reference genes is crucial to accurately evaluate and normalize the relative expression level of target genes for gene function analysis. However, commonly used reference genes have variable expression levels in developing skeletal muscle. There are few reports that systematically evaluate the expression stability of reference genes across prenatal and postnatal developing skeletal muscle in mammals. Here, we used quantitative PCR to examine the expression levels of 15 candidate refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 58 publications
1
18
1
Order By: Relevance
“…For the moderate expression target genes, RhoA also with a moderate expression level and highly stable expression profile was a good alternative normalizer. RhoA was also identified as suitable reference gene in neuroendocrine tumors of the lung (Niu et al, 2016), and in porcine skeletal muscle at 26 different developmental stages (Walter et al, 2016). However, we have not found that the other two novel reference genes TMN and MOB are used as internal controls in gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For the moderate expression target genes, RhoA also with a moderate expression level and highly stable expression profile was a good alternative normalizer. RhoA was also identified as suitable reference gene in neuroendocrine tumors of the lung (Niu et al, 2016), and in porcine skeletal muscle at 26 different developmental stages (Walter et al, 2016). However, we have not found that the other two novel reference genes TMN and MOB are used as internal controls in gene expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…All reactions were run in triplicate. miRNA expression was normalized to U6 RNA while the internal control gene for myogenin and Myh1 expression was β-Tubulin (Niu, Yang et al 2016). Relative expression was calculated by the comparative ΔΔCT method, and values were expressed as 2 −ΔΔCT (Livak and Schmittgen 2001).…”
Section: Rna Isolation Rt-pcr and Q-pcrmentioning
confidence: 99%
“…Quantitative PCR (qPCR) technology can quickly and accurately quantify the gene expression at transcriptional levels. The qPCR method has been reported to be more specific and powerful to determine the gene expression at different developmental stages or under different conditions [ 9 , 10 ]. However, the results of qPCR are affected by mRNA integrity and the efficiency of reverse transcription [ 11 ].…”
Section: Introductionmentioning
confidence: 99%